Os pais e seu filho portador de necessidades especiais - deficiência mental:um encontro inesperado - Góes, Fernando Antônio de Barros (2004)
The aim of this research was to study psychic presentations in father and/or mother of holder child of special necessities mentally disability, and consequently feelings of rejection/acceptance experienced by those parents, in those cases. Specificly, were analysed the conscious and unconscious behaviors and affections of parents related to those psychics presentations, among which, highlight: the wish of death, the feeling of guilty, the feeling of inferiority, the wish(and behaviors) of remedy and the refusal of reality (negation/disavowal), that were collected in the interviews did with the parents. The Theory of Psycho-analysis gave the opportunity to theoretical grounding to this study, being the parents speech analysed by psycho-analysis interpretation. After the analyse of different psychic presentations related to affections, already mentioned, it was possible to make up an ample point of view about the parents psychic conflict and to establish that it occurs an alternate movement of different psychic presentations, alternating acceptance/rejection about the child with special necessities. Those psychic presentations about the son with mentally disability are welcome in Ego in each one of parents, by three different ways: such as refusal (through defense mechanisms: Verneinung and Verleugnung ); such as a thing (that it isn t possible to say in words Unheimlich ); and such an appropriated establishment of reality, in other words, like holding mentally disability. It notices a dynamic with feedback, constant expression that alternate movement around the parent s rejection/acceptance about their child. It hopes this research gives theoretical support and pratical informations to professionals that do treatments to mentally disabled person and his family